Method for characterization of volatile organic compounds in the diet of Centris analis (Hymenoptera, Apidae, Centridini) immatures (Research, Society and Development, 2020)
This study tested three types of Solid-Phase Microextraction fibers in developing a method to extract volatile organic compounds present in the diet of immature Centris analis. Samples were placed in glass vials with metal lids and added with 3g NaCl and 8 ml deionized water. Extraction and characterization were carried out using a Headspace – Solid Phase Microextraction (HS-SPME) with Gas Chromatography – Mass Spectrometry, and the three types of fibers were polydimethylsiloxane (PDMS), divinylbenzene/ carboxen/ polydimethylsiloxane (DVB/CAR/PDMS) and carboxen/ polydimethylsiloxane (CAR/PDMS). Each type of fiber was exposed to volatiles for 30 min and analyzed in a chromatograph Agilent GC-MS equipped with a quadrupole detector (MSD 5977A), containing a HP-5MS (30 m x 0.25 mm x 0.25 µm) column and Helium as the carrier gas (1 ml.min-1). The CAR / PDMS fiber favored the extraction of volatile compounds to semi-volatile compounds, followed by DVB / CAR / PDMS, while PDMS presented a lower number of extracted compounds, which can be attributed to its apolar nature. The volatile compounds identified in the diet included alcohols, aldehydes, esters, ketones, and terpenes. The SPME technique has proven effective in the extraction of volatile organic compounds from immature of Centris analis diet, being the CAR/PDMS the most suitable fiber for this.